1993
DOI: 10.1073/pnas.90.8.3368
|View full text |Cite
|
Sign up to set email alerts
|

A regulatory cascade hypothesis for mammalian sex determination: SRY represses a negative regulator of male development.

Abstract: The mammalian Y chromosome carries the SRY gene, which determines testis formation. Here we review data on individuals who are XX but exhibit male characteristics: some have SRY; others do not. We have analyzed three families containing more than one such individual and show that these individuals lack SRY. Pedigree analysis leads to the hypothesis that they carry recessive mutations (in a gene termed Z) that allow expression of male characteristics. We propose that wild-type Z product is a negative regulator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
161
0
6

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(183 citation statements)
references
References 39 publications
16
161
0
6
Order By: Relevance
“…One such measure could be the function of SRY as an "anti-ovary" gene to antagonize Wnt/β-catenin signaling allowing normal testis differentiation in the XY gonad. A similar but more general hypothesis was put forward by McElreavey et al (McElreavey et al, 1993), who suggested that SRY may repress a negative regulator, termed "Z" of male development. Our data identifies a repressive "anti-ovary" function of SRY: the inhibition of the female-specific Wnt/β-catenin signaling pathway, where the Wnt/β-catenin signaling pathway is the negative regulator "Z" (Figure 7).…”
Section: Is Wnt/β-catenin the Proposed "Z" Factor?mentioning
confidence: 76%
See 1 more Smart Citation
“…One such measure could be the function of SRY as an "anti-ovary" gene to antagonize Wnt/β-catenin signaling allowing normal testis differentiation in the XY gonad. A similar but more general hypothesis was put forward by McElreavey et al (McElreavey et al, 1993), who suggested that SRY may repress a negative regulator, termed "Z" of male development. Our data identifies a repressive "anti-ovary" function of SRY: the inhibition of the female-specific Wnt/β-catenin signaling pathway, where the Wnt/β-catenin signaling pathway is the negative regulator "Z" (Figure 7).…”
Section: Is Wnt/β-catenin the Proposed "Z" Factor?mentioning
confidence: 76%
“…This observation also indicates that RSPO1 may have two complementary functions, a "pro-ovary" function in initiating female gonadal development and an "anti-testis" function in inhibiting the male gonadal development pathway (Chassot et al, 2008). Several years ago, the analysis of a number of XX male patients led McElreavey et al to propose that an unidentified female "Z" gene was involved in repressing male gonadal development and that SRY was actively involved in the repression of the "Z" gene in the XY gonad, allowing testis development to proceed (McElreavey et al, 1993). Therefore, it is possible that RSPO1 or downstream effectors of the RSPO1 signaling pathway could assume the function of the "Z" repressor gene (Bernard and Harley, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…Molecular genetics analyses have demonstrated that approximately 90 % of these patients carry a variable amount of Y material due to a Y-to-X interchange caused by an illegitimate recombination during paternal meiosis [13][14][15]. There was a report of an XX male caused by a translocation of an SRY gene fragment from the Y chromosome to an autosome [16].…”
Section: Results Of Pcr and Fishmentioning
confidence: 99%
“…Absence of Z would lead to SOX9 expression, testis development, and XX sex reversal. [14] We will come back to this idea below (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%